Serum pro-hepcidin levels in rheumatoid arthritis and systemic lupus erythematosus - Koca, Suleyman Serdar; Isik, Ahmet; Ustundag, Bilal; Metin, Kerem; Aksoy, Kader (Springer/Plenum Publishers, 2008)
Hepcidin is a principal iron regulatory hormone and its expression is stimulated by cytokines. The aim of this study was to determine serum levels of the prohormone form of hepcidin, pro-hepcidin, in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). The study included 72 RA and 28 SLE patients and 33 healthy controls (HQ. Serum iron status, tumor necrosis factor (TNF)-alpha, interleukin (IL)-6 and pro-hepcidin levels were determined. Pro-hepcidin levels in the RA group was higher than SLE and HC groups (p<0.05, p<0.001, respectively). Pro-hepcidin levels did not correlate with disease activity scores, cytokine levels and serum iron status in the RA and SLE groups, while it correlated with TNF-alpha, IL-6 and ferritin levels in the HC group (r=0.459, p<0.01, r=0.374, p<0.05, r=-0.603, p<0.01, respectively). Pro-hepcidin levels show extremely wide variations within the groups as do iron status and cytokines. Despite these wide variations correlation analysis do not reveal anything.
Keywords: anemia of chronic disease; pro-hepcidin; rheumatoid arthritis